STATUS OF PAIR LYMPH NODES IN MICE WITH SPONTANEOUS TUMORS OF HEMATOPOETIC SYSTEM - V. N. Manskikh (Сибирский онкологический журнал)
An asymmetry of renal lymph nodes involvement has been found in laboratory mice (BALB/c) with spontaneous blood neoplasms (lymphomas and leukemias). Left lymph node is more frequently involved and its enlargement (lymphadenopathy) is significantly more expressive in compare to right lymph node. The difference is not related to sex of animals and histological type of neoplasm. Microscopic pictures of the affected right and left lymph nodes also do not demonstrate differences. The involvement of other pair lymph nodes is not shown to be asymmetrical constantly. It seems that the asymmetry of renal lymph nodes involvement is related to more intensive glucocorticoids production by right adrenal gland in compare to left adrenal gland, consequently, higher level of antiproliferative adrenal hormones in lymph which drain from adrenal glands to ipsilateral lymph nodes.